EFFECT OF GELATINIZATION ACIDITY ON BIOPLASTIC SYNTHESIS OF GLUTINOUS RICE STARCH REINFORCED BY BAMBOO LEAF POWDER - Uma Fadzilia Arifin (Politek ATK Yogyakarta Press, 2022)
Bioplastic is organic-based plastics that offers eco-friendly and safe for human health properties. The plastic versatility in life requires the sustainable development of bioplastic synthesis to be carried out to produce bioplastics that can replace the function of plastics. One alternative for bioplastic synthesis is to produce biocomposite of glutinous rice starch reinforced by bamboo leaf powder. The parameters of bioplastic synthesis process have important role to produce bioplastics with certain characteristics. This research aims to study the effect of gelatization acidity on bioplastics synthesis from glutinous rice flour reinforced by bamboo leaf powder. The gelatinization process in bioplastic production was carried out under various acidity degree (pH 3, 4, 5, 6, and 7). The results showed that the recommended gelatinization process was under acidic conditions (pH 5) to obtain viscosity value was 208 cm2/s, water content was 34.27% and density was 1.326 g/mL. In addition, the pH value of 5 in gelatinization process also obtained tensile strength was 3.118 MPa and elongation percentage was 36.111% of bioplastic. Therefore, it can be concluded that the acidity of the gelatinization process affects the quality of the bioplastic produced.